2015
DOI: 10.15436/2378-6841.15.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organotin on Thyroid Morphophysiological Status

Abstract: Tributyltin is an environmental contaminant found in antifouling paints, widely used in ships and other vessels. TBT causes endocrine-disrupting effects in mammals, due to its possible transfer through marine food chains, and the consequent consumption of contaminated seafood. Thus, we aimed to evaluate whether the treatment with TBT could induce histophysiological changes in the thyroid gland. TBT promoted disorganization of parenchyma, fibrosis and vascular congestion in the gland. Moreover, morphometric ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Moreover, they demonstrated that TBTCl might inhibit TR expression in human HepG2 cells, both by direct action and by corepressor/coactivator inhibition/increase, such as nuclear receptor corepressor (NCoR) and steroid receptor coactivator (SRC-1), respectively. In contrast, Rodrigues-Pereira et al [40] verified TBT action on male Wistar rats and found that T4 levels were increased; this finding may be associated with type 2 deiodinase (D2) activity inhibition by TBT. The deiodinases, D1, D2, and D3, are responsible for the deiodination of T3 and T4 [46, 47].…”
Section: Otcs Effects In Th Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, they demonstrated that TBTCl might inhibit TR expression in human HepG2 cells, both by direct action and by corepressor/coactivator inhibition/increase, such as nuclear receptor corepressor (NCoR) and steroid receptor coactivator (SRC-1), respectively. In contrast, Rodrigues-Pereira et al [40] verified TBT action on male Wistar rats and found that T4 levels were increased; this finding may be associated with type 2 deiodinase (D2) activity inhibition by TBT. The deiodinases, D1, D2, and D3, are responsible for the deiodination of T3 and T4 [46, 47].…”
Section: Otcs Effects In Th Levelmentioning
confidence: 99%
“…Rodrigues-Pereira et al [40] verified TBT action on male Wistar rats that were treated orally with 500 ng/kg or 1000 ng/kg of TBT per day for 15 days. The authors found that animals treated with a larger dose of TBT showed apparent reduction in the follicle, colloid, and epithelium areas of the thyroid with a higher deposition of collagen.…”
Section: Disruptive Effect Of Otcs In the Thyroid Glandmentioning
confidence: 99%
See 2 more Smart Citations